2013
DOI: 10.15448/1983-652x.2013.1.11516
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de refrigerantes entre escolares de séries iniciais da cidade de Pelotas, Rio Grande do Sul

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…In addition, the child audience is the main target of indiscriminate advertisements linked to food and sugary drinks. 24 The media exerts a strong control on many behaviors of children Despite the methodological differences between the studies that were used to compare with the results achieved in this study, it was found that the consumption pattern of industrialized foods by children with less than two years of age, monitored by the nutritionist's office, is greater than that found in other studies analyzed, especially in those that refer to foods such as yogurt, instant noodles, coffee and soft drinks.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, the child audience is the main target of indiscriminate advertisements linked to food and sugary drinks. 24 The media exerts a strong control on many behaviors of children Despite the methodological differences between the studies that were used to compare with the results achieved in this study, it was found that the consumption pattern of industrialized foods by children with less than two years of age, monitored by the nutritionist's office, is greater than that found in other studies analyzed, especially in those that refer to foods such as yogurt, instant noodles, coffee and soft drinks.…”
Section: Introductionmentioning
confidence: 54%
“…16 By using the study above as a basis, it can be verified that the consumption of soup by the children analyzed in this study is with a higher index, since its introduction began in the age range of four months. 24 The II PPAM 9 found that only 48.9% of the hours prior to the survey. However, the introduction of other foods and beverages is early, occurring during the first weeks or months of life.…”
Section: Introductionmentioning
confidence: 98%
“…O estudo de D'Ávila e Kirsten (2017) mostrou que a presença de alimentos ultraprocessados nas cantinas escolares e a publicidade relacionada a eles, são fatores que contribuem com as escolhas e preferências dos escolares por estes alimentos, os quais são mais agradáveis ao paladar e de baixo preço quando comparados a alimentos naturais, além de demandarem um consumo excessivo por não suprirem as necessidades energéticas nessa faixa etária. Dados de um estudo realizado em Pelotas (RS) que analisou o consumo de refrigerante entre crianças do 1° ao 4° ano mostraram que 18,7% dos escolares, com excesso de peso, ingeriam refrigerantes diariamente, sendo o percentual encontrado neste estudo quase quatro vezes maior (75,0%) (FLORES, 2013). Logo, a obesidade vem se tornando um sério problema de saúde pública no Brasil e no mundo, afetando crianças de todas as idades, classes sociais, raças e etnias (FREITAS, 2014).…”
Section: Discussionunclassified
“…Alimentos como doces e refrigerantes são considerados menos saudáveis, pois sua ingestão ocasiona um alto consumo calórico (34,35) . Alguns estudos tentam buscar evidências de que o consumo excessivo de açúcares pode causar efeitos prejudiciais à saúde, todavia, a associação mais consistente tem sido entre uma alta ingestão de açúcar ou bebidas adoçadas e o desenvolvimento de obesidade (36,37) .…”
Section: Discussionunclassified